2008
DOI: 10.1002/gps.2167
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalae morphometry in late‐life depression

Abstract: SUMMARYObjective The amygdalae have been a focus of mood disorder research due to their key role in processing emotional information. It has been long known that depressed individuals demonstrate impaired functional performance while engaged in emotional tasks. The structural basis for these functional differences has been investigated via volumetric analysis with mixed findings. In this study, we examined the morphometric basis for these functional changes in late-life depression (LLD) by analyzing both the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…The posteromedial cortical nucleus was greater in the male rat [37] while there was no difference in basolateral nucleus [28]. Results of our shape analysis are generally in line with these prior animal studies on sex differences [14,28,37]. Men and women are different in cognition and emotional event processing and have a different neural basis for these processes [9,20,35].…”
supporting
confidence: 81%
See 1 more Smart Citation
“…The posteromedial cortical nucleus was greater in the male rat [37] while there was no difference in basolateral nucleus [28]. Results of our shape analysis are generally in line with these prior animal studies on sex differences [14,28,37]. Men and women are different in cognition and emotional event processing and have a different neural basis for these processes [9,20,35].…”
supporting
confidence: 81%
“…Previous rodent studies reported that the volume of the posterodorsal medial nucleus in the amygdala of the male rodents was larger than that of the female [14], which may have been affected by androgen [11]. The posteromedial cortical nucleus was greater in the male rat [37] while there was no difference in basolateral nucleus [28]. Results of our shape analysis are generally in line with these prior animal studies on sex differences [14,28,37].…”
mentioning
confidence: 99%
“…These same investigators reported that amygdalar volumes were decreased in late-life depressive illness patients and that these volumetric reductions were predictive of treatment responsiveness (Sheline et al, 2012). Additional studies reported similar decreases in amygdalar volumes in late-life depressive illness patients (Andreescu et al, 2008;Burke et al, 2011), while other studies suggested that late-life depression was associated with changes in amygdalar shape (Tamburo et al, 2009). These studies and others (von Gunten et al, 2000;Hastings et al, 2004) support the concept that decreases in amygdalar volume is a neuroanatomical deficit characteristic of major depressive illness.…”
Section: Analyses Of Amygdalar Volumetric Changes In Depressive Illnementioning
confidence: 66%
“…This is due to the fact that while most volumetric analyses of subcortical structures look at the entire structure, shape provides an advantage in its vertex-wise approach (Voineskos et al, 2015). Comparison studies of methodologies support this having found that while volume measures indicated no differences between populations, shape metrics did (Tamburo et al, 2009;Posener et al, 2003).…”
Section: Social Cognition Factor Correlates: Hippocampus and Amygdalamentioning
confidence: 99%